Strategic Plan Development for the Implementation of Balanced Scorecard as a Performance Measuring Instrument at Gotong Royong Hospital Surabaya - Indah Puji Lestari; Nur Fadjrih Asyik; Titik Mildawati (Budapest International Research and Critics University, 2021)
This study aims to determine the development of a strategic plan from the evaluation results of implementing the balanced scorecard as a performance measurement tool at the Gotong Royong Hospital, Surabaya. This type of research uses descriptive qualitative. This data collection technique is carried out through (1) Interview (2) Documentation. The data source of this research from primary data. The analysis of the application of the balanced scorecard is to find out how the company is performing, then identify the internal and external environment to determine the key factors. After obtaining the key factors, they are evaluated using the EFE Matrix, IFE Matrix, TOWS Matrix, and IE Matrix, which is then obtained the recommended alternative strategies. The results of the recommended priority strategy alternatives are assessed using QSPM Matrix. The results Analysis using the EFE Matrix, IFE Matrix, TOWS Matrix, IE Matrix and QSPM then obtained the chosen strategy, namely product development and market penetration strategies. Based on the TOWS analysis, the reserachers provide recommendations that can be used to strengthen the strengths and opportunities as well as control weaknesses and threats by developing 13 strategies chosen.